2012
DOI: 10.1016/j.na.2012.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Positive ground state solutions for the critical Klein–Gordon–Maxwell system with potentials

Abstract: This paper deals with the Klein-Gordon-Maxwell system when the nonlinearity exhibits critical growth. We prove the existence of positive ground state solutions for this system when a periodic potential V is introduced. The method combines the minimization of the corresponding Euler-Lagrange functional on the Nehari manifold with the Brézis and Nirenberg technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…For the critical growth case, that is, f (z) = μ|z| p-2 z + |z| 4 z, Cassani [6] showed that the above system has at least a radially symmetric solution when 4 < p < 6 or p = 4 provided that μ > 0 is sufficiently large. Soon after that, Carrião et al [5] also studied the existence of a radially symmetric solution for 2 < p < 6, which extended and generalized the results in [1] and [6], respectively. Recently, He [12] considered the following nonlinear Klein-Gordon-Maxwell system with non-constant external potential:…”
Section: Introduction and Main Resultsmentioning
confidence: 83%
“…For the critical growth case, that is, f (z) = μ|z| p-2 z + |z| 4 z, Cassani [6] showed that the above system has at least a radially symmetric solution when 4 < p < 6 or p = 4 provided that μ > 0 is sufficiently large. Soon after that, Carrião et al [5] also studied the existence of a radially symmetric solution for 2 < p < 6, which extended and generalized the results in [1] and [6], respectively. Recently, He [12] considered the following nonlinear Klein-Gordon-Maxwell system with non-constant external potential:…”
Section: Introduction and Main Resultsmentioning
confidence: 83%
“…This type of equation has very interesting physical background which is a model to describe the nonlinear Klein–Gordon field interacting with the electromagnetic field. Along with the development of variational methods, many mathematicians used these methods to investigate the existence and multiplicity of solutions for differential equations equations(see [1, 2, 5–24, 26, 28]). In 2001, V. Benci and D. Fortunato [5] considered the following systems truerightleftnormalΔu+true[m2false(ω+ϕfalse)2true]u=false|ufalse|q2uleftin4.ptR3,leftnormalΔϕ+ϕu2=ωu2leftin4.ptR3.By using the variational methods, they obtained infinitely many solitary wave solutions when |m|>|ω| and 4<q<6.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Ground state solutions, semiclassical state solutions, nonradial solutions have been studied in [7][8][9][10]. The critical exponent case have also been considered in [11][12][13][14]. In [15], via the Ekeland variational principle and the mountain pass theorem, two nontrivial solutions for a nonhomogeneous Klein-Gordon-Maxwell system were got by Chen and Tang.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%